Identification of Bacteria in Two Food Waste Black Soldier Fly Larvae Rearing Residues - Gold, Moritz; von Allmen, Fabienne; Zurbrügg, Christian; Zhang, Jibin; Mathys, Alexander (Frontiers in Microbiology, 2020)
Significant economic, environmental, and social impacts are associated with the avoidable disposal of foods worldwide. Mass-rearing of black soldier fly (Hermetia illucens) larvae using organic wastes and food- and agro-industry side products is promising for recycling resources within the food system. One current challenge of this approach is ensuring a reliable and high conversion performance of larvae with inherently variable substrates. Research has been devoted to increasing rearing performance by optimizing substrate nutrient contents and ratios, while the potential of the substrate and larval gut microbiota to increase rearing performance remains untapped. Since previous research has focused on gut microbiota, here, we describe bacterial dynamics in the residue (i.e., the mixture of frass and substrate) of black soldier fly larvae reared on two food wastes (i.e., canteen and household waste). To identify members of the substrate and residue microbiota, potentially associated with rearing performance, bacterial dynamics were also studied in the canteen waste without larvae, and after inactivation by irradiation of the initial microbiota in canteen waste. The food waste substrates had similar microbiota; both were dominated by common lactic acid bacteria. Inactivation of the canteen waste microbiota, which was dominated by Leuconostoc, Bacillus, and Staphylococcus, decreased the levels of all rearing performance indicators by 31-46% relative to canteen waste with the native microbiota. In both food waste substrates, larval rearing decreased the bacterial richness and changed the physiochemical residue properties and composition over the rearing period of 12 days, and typical members of the larval intestinal microbiota (i.e., Providencia, Dysgonomonas, Morganella, and Proteus) became more abundant, suggesting their transfer into the residue through excretions. Future studies should isolate members of these taxa and elucidate their true potential to influence black soldier fly mass-rearing performance.